Retinoid based nanoemulsions: Preparation to therapeutic applications - Ayesha Rauf; Muhammad Jamshaid; Mahmood Ahmad; Irfan Bashir (AMMANIF, 2021)
Modern mode of drug delivery system has been constructed to defeat the main issues linked with the traditional drug delivery system. This particular review will give an idea about the retinoid based nanoemulsion system. The main focus is to briefly explain the different aspects of nanoemulsion formulations, procedure of preparation, portrayal procedures with special focus on different utilizations of nanoemulsion in various area. Nanoemulsions are colloidal dispersion system that are composed of two non-miscible mixtures mixed along with surfactants and co-surfactants emulsifier to develop a single phase which is thermodynamically balanced. Nanoemulsion droplet sizes commonly fall in the range of 20-200 nm and show thin size distributions. Nanoscale dispersions of droplets of one liquid in another insoluble liquid can be achieved by using extreme emulsification procedures. Retinoid, better known as vitamin A are lipophillic in nature. They are vastly used for therapeutic purpose in skin disorders. Retinoid are among one of the fundamental compound found in cosmeceuticals. They are the most investigated compound with sufficient information supporting them. Retinoid include natural or synthetic derivatives that decrease hyper pigmentation and limit collagen breaking enzymes. Nanoemulsions comprise of tiny oil-in-water globules, having less than 100 nm diameter. They are delicate frameworks by nature. Traditional formulations are restricted because of irritation, poor aqueous solubility and high instability of retinoid. But administration of retinoid in aqueous media is enabled due to nanoemulsion based formulation, decreasing degradation, controlled release, high stability, improve targeting and enhance efficacy. Nanoemulsion show incredible guarantee for the future of beauty care products, diagnostics, treatments, and biotechnologies. The unique properties of nanoemulsions such as high stability, translucent appearance and efficient drug delivery attribute has attracted researchers interest which is one of the reason why the usage of nanoscale emulsion has grown rapidly during the recent decades. Nanoemulsion formulation might be considered as viable, safe and with enhanced bioavailability. Comparing to the conventional topical formulation, nanoemulsion possess advance transdermal permeation of various drugs such as gels and emulsions. Nanoemulsion is significantly important in modern pharmaceutical industry and provide many benefits in drug delivery systems. This review is focused on the most recent literature on developments of retinoid based nanoemulsions.